Effect of the polishing procedure and surface sealant application on fluoride release - Ugurlu, Muhittin (Brazilian Dental Science, 2020)
Objective: This study aimed to assess the effect of the polishing procedure and surface sealant application on the fluoride release of restorative materials. Material and Methods: The groups were consisted of using five different restorative materials were employed: Beautifil II, GCP Glass Fill, Amalgomer CR, Zirconomer and Fuji IX GP. 30 disk-shaped specimens (8x2 mm) were prepared from each material. Each group was subdivided into three groups considering finishing procedures: Mylar strip, polishing with Super-Snap discs, G-Coat Plus application after polishing with Super-Snap discs. The amount of fluoride released into distilled water was measured using a fluoride ion-selective electrode and ion analyzer after 24 hours, followed by measurement on days 3, 7, 15, 21, and 28.  Surface analysis of the materials was performed with SEM (Scanning Electron Microscopy) and EDS (Energy Dispersive X-ray Spectroscopy). The data were statistically analyzed using two-way repeated measure ANOVA and LSD test (p=0.05). Results: The highest amount of fluoride released was measured after the first 24 h for all materials. Beautifil II released less fluoride than other materials in all measurement periods (p